Palladium-loaded Renewable Polymer as a Green Heterogeneous Catalyst for Cross-coupling Reactions under Microwave Irradiation. (December 2014) - Pan, Dan; Wu, Aiqun; Li, Pengfei; Xu, Haitang; Lei, Fuhou; Shen, Liqun
A new palladium catalyst was prepared by immobilising ligand 2, 2′-dipyridylamine on the backbone of an acidic rosin polymer from gum rosin, on to which palladium(II) was bound via coordination. The catalyst at a low loading of 0.2 mol% was found to be highly effective for Suzuki–Miyaura coupling reactions of aryl halides and arylboronic acids under microwave irradiation in the presence of 1 equiv. of Na2 CO3, affording excellent yields of the corresponding biaryls. Moreover, the catalyst exhibited very good recyclability over three cycles.